2003
DOI: 10.1159/000068228
|View full text |Cite
|
Sign up to set email alerts
|

Demineralization of Er:YAG and Er,Cr:YSGG Laser-Prepared Enamel Cavities in vitro

Abstract: The aim of the present study was to establish whether cavity preparation by means of an erbium laser with efficient water cooling is capable of reducing the susceptibility of the prepared dental enamel to demineralization and thus of achieving a potential caries-protective effect in the region of cavity margins. To this end, cavities limited to the enamel were prepared in the crowns of 10 teeth each using an Er:YAG (λ = 2,940 nm) and an Er,Cr:YSGG laser (λ = 2,780 nm). A control cavity prepared conventionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 10 publications
0
39
1
10
Order By: Relevance
“…Hossain et al 16 found that the knoop hardness of the cavity floors prepared by Er:YAG laser was comparable to that of the conventional bur cavity. Apel et al 29 concluded that cavity preparation by means of an erbium laser would offer no benefits in the sense of resistance to secondary caries formation in the clinical situation. The differences observed between the outcomes of this study and those of previous authors could be attributed to the laser parameters employed such as pulse energy and duration, pulse repetition rate, duration of laser irradiation and application of water cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Hossain et al 16 found that the knoop hardness of the cavity floors prepared by Er:YAG laser was comparable to that of the conventional bur cavity. Apel et al 29 concluded that cavity preparation by means of an erbium laser would offer no benefits in the sense of resistance to secondary caries formation in the clinical situation. The differences observed between the outcomes of this study and those of previous authors could be attributed to the laser parameters employed such as pulse energy and duration, pulse repetition rate, duration of laser irradiation and application of water cooling.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of laser-prepared cavities leads to an increased area of adhesive interface, which likely takes more time to be degraded. Also, the Er:YAG laser-treated surface presents fusion and sealing of the enamel micropores (20) and, consequently, a reduction in solubility (21,22). This is despite the action of acid etching that dissolves the hydroxyapatite (23), which may leave the adhesive interface vulnerable to hydrolytic degradation (10).…”
Section: Discussionmentioning
confidence: 99%
“…4*,10 demostraron en estudios in vitro que los dientes tratados con Er:YAG y con Er,Cr:YSGG eran más resistentes al ataque ácido y por lo tanto aumentaba la resistencia de estos dientes frente a las caries secundarias. Sin embargo otros autores como Apel y cols 12 no han podido confirmar que el uso de los láse-res de erbio en la preparación de cavidades dentarias ofrezcan esta importante ventaja.…”
Section: Terapéutica Dental Preparación De Cavidadesunclassified